Teori Pembuktian Dalam Sistem Hukum Nasional - Afrillia Bella Novita; Alvina Damayanti Riyanto; A Frada Ali H Al Ghifari (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Evidence The Criminal Procedure Code considers witness statements at trial as the main evidence. Almost all evidence in criminal cases is always based on examination of testimony, even though testimony is not the only means of evidence, but evidence by testimony is still needed, at least in addition to other means of evidence by testimony. Under Article 160(3) of the Criminal Procedure Code, witnesses must take an oath or promise in accordance with their respective religious procedures before they can testify. If the witness does not take an oath according to religious procedures, then the oath is null and void by law. This is because Article 160(3) of the Criminal Procedure Code stipulates that an oath must be taken. According to Witness Religion. While Persid Ahmadiyah was being investigated at Muhammad His Asep His Abdullahman alias Utep and the Bandung District Court, the actions of the judge investigating the case were reported to the Judicial Commission. The report was made in connection with a complaint by the Indonesian Ahmadiyya Order (JAI) that five JAI members were used as witnesses in court, but the judicial authority that reviewed the case said the witnesses had no religion. It does not allow oaths to be taken according to religion. Witness, namely Islam.